Study of Palm Sugar Farming Business in Bontomanai Village Bungaya District Gowa Regency - Firdayanti, Firdayanti; Ridwan, Ridwan; Sabar, Adrayanti (JURNAL ILMU-ILMU KEHUTANAN, 2023)
Palm sugar is one of the products from aren (Arenga pinnata) which is classified as Non-Timber Forest Products (NTFPs) which has the potential to empower the community's economy. This research was conducted in Bontomanai Village, Bungaya District, Gowa Regency. The purpose of this study is to describe the management of palm sugar and calculate the income of palm sugar farmers. Descriptive analysis approach and income analysis are used as methods in analyzing the data obtained. The results showed that the process of managing palm sap into palm sugar was still managed in a simple and traditional way. The stages of managing palm sugar production which include tapping, cooking, printing, to packaging. Meanwhile, the total income of palm sugar is Rp. 361,081,967 per year with an average of Rp 9,758,967/household/year. The level of education of aren farmers, the productive age group, and the percentage of family dependents are an integral part of the results of this study. Key words:Palm Sugar, HHBK, Income, Management, Farmer